2012
DOI: 10.5398/medpet.2012.35.2.96
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Single Nucleotide Polymorphism in Exon 4 of Insulin-Like Growth Factor-1 Associated with Production Traits in Bali Cattle

Abstract: ABSTRAKInsulin-like growth factor-1 (IGF-1) adalah salah satu kandidat gen dalam strategi seleksi menggunakan marka DNA (marker assisted selection). Strategi kandidat gen merupakan teknik biologi molekuler untuk mengidentifikasi lokus sifat kuantitatif secara langsung, dengan asumsi bahwa variasi genetik kandidat gen ini berasosiasi dengan sifat kuantitatif. Penelitian ini dirancang untuk mengidentifikasi adanya mutasi baru pada exon 4 yang dapat menimbulkan polimorfisme gen IGF-1 yang mempengaruhi sifat produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Yurnalis et al (2017) from a study in local Pesisir cattle in West Sumatera reported frequencies of AA, AB, and BB genotypes were successively 0.0125, 0.0125, and 0.9750 and resulted frequencies of A and B alleles were 0.00625, and 0.99375 respectively. Genetic polymorphism of IGF-I gene was also reported from Bali cattle of which an SNP as a transition mutation T/C being identified by restriction enzyme RsaI at exon 4 with the frequency of C allele higher than that of T allele, namely 0.836 vs. 0.164 (Maskura et al 2012). Furtherly genotyping IGF1 by PCR -RFLP method using TaqI and MspI restriction enzymes and amplification-created restriction site (ACRS) one by SnaBI, TasI and TaqI restriction enzymes in Poland Cattle, Szewczuk (2016) reported frequencies of the most common alleles by 0.67 for T allele (IGF1|SnaBI), 0.85 for A allele (IGF1|TasI), 0.95 for C allele (IGF1R|TaqI), 0.84 for G allele (IGF1R|MspI) and 0.69 for G allele (IGF1R|TaqI).…”
Section: Genotype and Allele Frequencymentioning
confidence: 97%
“…Yurnalis et al (2017) from a study in local Pesisir cattle in West Sumatera reported frequencies of AA, AB, and BB genotypes were successively 0.0125, 0.0125, and 0.9750 and resulted frequencies of A and B alleles were 0.00625, and 0.99375 respectively. Genetic polymorphism of IGF-I gene was also reported from Bali cattle of which an SNP as a transition mutation T/C being identified by restriction enzyme RsaI at exon 4 with the frequency of C allele higher than that of T allele, namely 0.836 vs. 0.164 (Maskura et al 2012). Furtherly genotyping IGF1 by PCR -RFLP method using TaqI and MspI restriction enzymes and amplification-created restriction site (ACRS) one by SnaBI, TasI and TaqI restriction enzymes in Poland Cattle, Szewczuk (2016) reported frequencies of the most common alleles by 0.67 for T allele (IGF1|SnaBI), 0.85 for A allele (IGF1|TasI), 0.95 for C allele (IGF1R|TaqI), 0.84 for G allele (IGF1R|MspI) and 0.69 for G allele (IGF1R|TaqI).…”
Section: Genotype and Allele Frequencymentioning
confidence: 97%
“…The further study regarding to detect SNP along IGF1 gene is important for developing marker assisted selection (MAS) to improve productivity traits of Pasundan cattle in the future. Several studies reported that the polymorphism of bovine IGF1 gene were occured in exon 4 and had associated with production traits in Bali cattle (Maskur et al 2012). Mullen et al (2011) reported that polymorphisms of bovine IGF1 gene were occured in 5' UTR, intron and 3' UTR.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, (Lynch et al , 2010) SNPs, IGFi1A-T, IGFi2C-T, IGFi3G-A, in IGF-1 were associated with milk production traits and BCS; and are in the agreement with our findings. Other studies reported that the polymorphism of bovine IGF-1 gene in exon 4 were associated with production traits in Bali cattle (Maskur et al ., 2012) but polymorphism in the intron 4 of IGF-1 gene was not associated with production traits in mixed population of Charolais and Beef master cattle (Reyna et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%